Prediction of Photochemically Produced Reactive Intermediates in Surface Waters via Satellite Remote Sensing - Chen, Yiling; Hozalski, Raymond M; Olmanson, Leif G; Page, Benjamin P; Finlay, Jacques C; Brezonik, Patrick L; Arnold, William A (Environmental science & technology, 2020)
Absorption of solar radiation by colored dissolved organic matter (CDOM) in surface waters results in the formation of photochemically produced reactive intermediates (PPRIs) that react with pollutants in water. Knowing the steady-state concentrations of PPRIs ([PPRI] ) is critical to predicting the persistence of pollutants in sunlit surface waters. CDOM levels ( ) can be measured remotely for lakes over large areas using satellite imagery. Laboratory measurements of [PPRI] and apparent quantum yields (Φ) of three PPRIs ( DOM*, O , and OH) were made for 24 lake samples under simulated sunlight. The total rate of light absorption by the water samples ( ), the rates of formation ( ), and [PPRI] of DOM* and O linearly increased with incre sing . The production rate of OH was linearly correlated with , but the steady-state concentration was best fit by a logarithmic function. The relationship between measured and Landsat 8 reflectance was used to map for more than 10 000 lakes across Minnesota. Relationships of with , [PPRIs] , and were coupled with satellite-based assessments to map reactive species production rates and concentrations as well as contaminant transformation rates. This study demonstrates the potential for using satellite imagery for estimating contaminant loss via indirect photolysis in lakes.